2001
DOI: 10.1097/00003246-200105000-00024
|View full text |Cite
|
Sign up to set email alerts
|

Nebulized sildenafil is a selective pulmonary vasodilator in lambs with acute pulmonary hypertension

Abstract: Nebulized sildenafil is a selective pulmonary vasodilator that can potentiate the pulmonary vasodilating effects of inhaled NO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
71
2
5

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 160 publications
(85 citation statements)
references
References 15 publications
7
71
2
5
Order By: Relevance
“…While still effective in post op patients, the overall effect of inhaled NO and sildenafil was not significantly different. In contrast to previous animal studies 18,19 we found no significant effects on intrapulmonary shunting in our cath laboratory patients, but this was clearly an important issue in postoperative mechanically ventilated patients. In the presence of alveolar hyperoxia, the fall in arterial pO 2 was statistically significant, but was not associated with clinically relevant hypoxemia.…”
Section: Intravenous Sildenafil Compared With Inhaled No As a Specificontrasting
confidence: 99%
“…While still effective in post op patients, the overall effect of inhaled NO and sildenafil was not significantly different. In contrast to previous animal studies 18,19 we found no significant effects on intrapulmonary shunting in our cath laboratory patients, but this was clearly an important issue in postoperative mechanically ventilated patients. In the presence of alveolar hyperoxia, the fall in arterial pO 2 was statistically significant, but was not associated with clinically relevant hypoxemia.…”
Section: Intravenous Sildenafil Compared With Inhaled No As a Specificontrasting
confidence: 99%
“…In a lamb model of acute pulmonary hypertension, inhalation of nebulized sildenafil reduced pulmonary artery pressures significantly and had a synergistic effect with inhalation of nitric oxide, whereas pulmonary right-to-left shunt volume did not increase after sildenafil. 49 However, a recent study performed in normal pigs described an increase in right-to-left shunt volume and subsequently a decrease of systemic arterial oxygen tension after sildenafil, along with reduced pulmonary arterial pressure after sildenafil. 50 These experimental data suggest that at least in certain conditions with increased pulmonary arterial pressure, PDE 5 inhibition might be of benefit, and the possibility of additional inhalative application of other agents used to lower pulmonary artery pressure might provide a unique approach to achieve site-specific, additive, or even overadditive effects.…”
Section: Effects Of Pde 5 Inhibition On Pulmonary Vasculaturementioning
confidence: 96%
“…No animal had an intracardiac shunt, which could potentially influence (or limit) any acute effect of an intravenous pulmonary vasodilator upon oxygenation. However, a number of previous investigations of pulmonary vasodilators in models of acute pulmonary hypertension (27,29,41) and, specifically, therapies for meconium aspiration syndrome (42,43) have been explored in more mature animals. Indeed, having demonstrated an acute rise in ET-1 levels coincident with an increase in PVR after meconium aspiration, it would seem appropriate to investigate the subsequent actions of an ET-A receptor antagonist in our model.…”
Section: Discussionmentioning
confidence: 99%